2017
DOI: 10.1109/tia.2016.2645888
|View full text |Cite
|
Sign up to set email alerts
|

Multiagent-Based Distributed State of Charge Balancing Control for Distributed Energy Storage Units in AC Microgrids

Abstract: In this paper, a multiagent based distributed control algorithm has been proposed to achieve state of charge (SoC) balance of distributed energy storage (DES) units in an AC microgrid. The proposal uses frequency scheduling instead of adaptive droop gain. Each DES unit is taken as an agent and they schedule their own frequency reference given of the real power droop controller according to the SoC values of the other DES units. Further, to obtain the average SoC value of DES, dynamic average consensus algorith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
61
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(63 citation statements)
references
References 21 publications
(14 reference statements)
0
61
0
2
Order By: Relevance
“…As a result, it is important to maintain that level when EVs are operating in the decentralised mode. According to [36], the SOC of a battery is a function of time and output current of the battery i.e. SOC n = f (t, i n Batt ).…”
Section: Need-based Distributed Coordination Strategymentioning
confidence: 99%
“…As a result, it is important to maintain that level when EVs are operating in the decentralised mode. According to [36], the SOC of a battery is a function of time and output current of the battery i.e. SOC n = f (t, i n Batt ).…”
Section: Need-based Distributed Coordination Strategymentioning
confidence: 99%
“…This problem is also observed in the microgrid or wind farm systems with multiple BESSs that are operated independently. Several studies have addressed the issue of SOC imbalance in the independent BESSs [12][13][14][15][16][17][18][19][20][21][22]. The SOC of the BESSs is unbalanced due to the difference of wind power output, initial SOC, capacities of BESSs, and line impedances [12].…”
Section: Introductionmentioning
confidence: 99%
“…In order to deal with the unbalanced SOC problem, several control strategies for SOC balancing have been introduced [15][16][17][18][19][20][21][22]. The SOC-based droop control strategies of the converter have been used widely to achieve proper power sharing and SOC balancing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With rapid development of EV, battery cell balancing has attracted much attention. Researches on battery balancing mainly include balancing methods [4,5,6,7,8], strategies [9,10,11,12] and control algorithms [13,14,15,16]. Related reviews can be found in [17,18,19].…”
Section: Introductionmentioning
confidence: 99%